2023
DOI: 10.3389/fnut.2023.1037200
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia: Molecular regulatory network for loss of muscle mass and function

Abstract: Skeletal muscle is the foundation of human function and plays a key role in producing exercise, bone protection, and energy metabolism. Sarcopenia is a systemic disease, which is characterized by degenerative changes in skeletal muscle mass, strength, and function. Therefore, sarcopenia often causes weakness, prolonged hospitalization, falls and other adverse consequences that reduce the quality of life, and even lead to death. In recent years, sarcopenia has become the focus of in-depth research. Researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Also, research has shown a connection between Atrogin-1/MAFbx and cardiac hypertrophy [ 38 ]. MuRF-1 have been identified as essential enzymes in ubiquitin-mediated proteolysis and muscle atrophy, and modulating their expression via physical activity or targeting the upstream cytokines and growth factors that regulate their expression has the potential to prevent or reverse muscle atrophy in patients with sarcopenia [ 39 , 40 ]. The key mechanism is made up by the acceleration of muscle protein degradation in muscle involving an increase in the expression and activity of two muscle-specific, E3 Ub ligases, Atrogin-1 (also known as MAFbx) and MuRF-1 [ 34 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, research has shown a connection between Atrogin-1/MAFbx and cardiac hypertrophy [ 38 ]. MuRF-1 have been identified as essential enzymes in ubiquitin-mediated proteolysis and muscle atrophy, and modulating their expression via physical activity or targeting the upstream cytokines and growth factors that regulate their expression has the potential to prevent or reverse muscle atrophy in patients with sarcopenia [ 39 , 40 ]. The key mechanism is made up by the acceleration of muscle protein degradation in muscle involving an increase in the expression and activity of two muscle-specific, E3 Ub ligases, Atrogin-1 (also known as MAFbx) and MuRF-1 [ 34 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as animals age, there is a gradual decline in their muscle mass, strength, and function, resulting in a condition known as sarcopenia. 6 , 7 Although the factors contributing to sarcopenia have been investigated from various aspects, including alterations in muscle protein synthesis, mitochondrial function, and inflammation, 8 there has been limited exploration of the structural changes in Z-disks and M-lines associated with sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Muscle atrophy is primarily caused by an imbalance between protein synthesis and degradation. 7 Ubiquitin-proteasome system (UPS) activation leads to increased protein degradation within muscles and is closely associated with skeletal muscle atrophy. 8 One characteristic of muscle atrophy is a reduction in myofibrillar proteins because of excessive activation of the ubiquitin–proteasome pathway, which often manifests by increased expression of muscle-specific ubiquitin ligases Fbxo32 (Atrogin-1, MAFbx) and Trim63 (MuRF1), 9 which are recognized as pivotal genes in the regulation of muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%